2010
DOI: 10.1103/physreva.82.010101
|View full text |Cite
|
Sign up to set email alerts
|

Switching Casimir forces with phase-change materials

Abstract: We demonstrate here a controllable variation in the Casimir force. Changes in the force of up to 20% at separations of ~100 nm between Au and AgInSbTe (AIST) surfaces were achieved upon crystallization of an amorphous sample of AIST. This material is well known for its structural transformation, which produces a significant change in the optical properties and is exploited in optical data storage systems. The finding paves the way to the control of forces in nanosystems, such as micro-or nanoswitches by stimul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
171
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(175 citation statements)
references
References 32 publications
4
171
0
Order By: Relevance
“…[45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin. 31 In this respect we would like to note that the calibration consists in determination of the parameters of a setup using well established physical laws (in our case of electrostatics) and involves only well understood and precisely measured forces.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45][46][47][48]52 It was claimed that anomalous dependences of the residual potential difference and separation on contact on the separation distance observed in several experiments cast doubts on the measurements of the Casimir force performed to date. It was also suggested that inasmuch electrostatic calibrations are based on a fitting procedure there is no principal difference detween independent measurements of the Casimir force [20][21][22][23][24][25][26][27][28][29][30][35][36][37][39][40][41][42][43][44]71 and deriving the Casimir force by means of a fit from some much larger measured force of hypothetical origin. 31 In this respect we would like to note that the calibration consists in determination of the parameters of a setup using well established physical laws (in our case of electrostatics) and involves only well understood and precisely measured forces.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][40][41][42][43][44] The AFM system consists of a head, piezoelectric actuator, an AFM controller and computer. The head includes a diode laser which emits a collimated beam with a waist of tens of micrometers at the focus, an Au-coated cantilever with attached sphere that bends in response to the sphere-plate force, and photodetectors which measure the cantilever deflection through a differential measurement of the laser beam intensity.…”
Section: A Schematic Of the Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] discussed measurements of the gradient of the Casimir force in a linear regime (the same regime was employed in dynamic measurements by means of an atomic force microscope [49][50][51][52][53]). Here, we find the frequency shift of an oscillator, caused by the Casimir force between an elliptic cylinder and a plate, in the nonlinear regime.…”
Section: An Asymmetric Cylindrical Lens and A Platementioning
confidence: 99%
“…In some cases tabulated optical data were taken into account. [27][28][29] In this paper, we will explore the actuation dynamics of microswitches made from real materials (with a definite measured optical response [41][42][43] and characterized by some degree of nanoscale roughness), accounting for both electrostatic and Casimir forces, which counteract an elastic restoring force [see Fig. 1(a)].…”
Section: Introductionmentioning
confidence: 99%